2022
DOI: 10.1097/shk.0000000000002029
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the Innate Immune Response in Skeletal Muscle to Sepsis-Induced Alterations in Protein Balance

Abstract: There is growing appreciation that skeletal muscle is a fully functional component of the body's innate immune system with the potential to actively participate in the host response to invading bacteria as opposed to being a passive target. In this regard, skeletal muscle in general and myocytes specifically possess an afferent limb that recognizes a wide variety of host pathogens via their interaction with multiple classes of cell membrane–bound and intracellular receptors, including toll-like receptors, cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 132 publications
0
7
0
Order By: Relevance
“…Inflammation is one of the main drivers of sepsis‐induced muscle atrophy. [ 2 , 25 ] Here, we found that both septic WT and ZBED6 −/− pigs developed persistent fever (Figure S4A , Supporting Information), leukocytosis, and neutrophilia (Figure S4B,C , Supporting Information), as well as similar mRNA levels of inflammatory marker genes IL‐6, TNF‐a, NLRP3, and TLR4 in skeletal muscle (Figure S4D–F , Supporting Information). These results demonstrated that ZBED6 expression is not related to inflammatory, excluding a potential contribution of attenuation of systemic or skeletal muscle specific inflammation to the protection of sepsis‐induced muscle atrophy by ZBED6 deletion.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Inflammation is one of the main drivers of sepsis‐induced muscle atrophy. [ 2 , 25 ] Here, we found that both septic WT and ZBED6 −/− pigs developed persistent fever (Figure S4A , Supporting Information), leukocytosis, and neutrophilia (Figure S4B,C , Supporting Information), as well as similar mRNA levels of inflammatory marker genes IL‐6, TNF‐a, NLRP3, and TLR4 in skeletal muscle (Figure S4D–F , Supporting Information). These results demonstrated that ZBED6 expression is not related to inflammatory, excluding a potential contribution of attenuation of systemic or skeletal muscle specific inflammation to the protection of sepsis‐induced muscle atrophy by ZBED6 deletion.…”
Section: Resultsmentioning
confidence: 76%
“…Up to 90% of severe sepsis patients have muscle atrophy that hampers weaning from ventilatory support, delays rehabilitation, and is associated with an increased risk of death. [ 1 ] Although various contributing factors such as inflammation, [ 2 ] oxidative stress [ 3 ] and mitochondrial dysfunction, [ 4 ] and protein metabolism imbalance [ 5 ] have been identified, the molecular regulators involved in modulating muscle atrophy remain poorly understood. Several animal models, such as pig, [ 6 ] rat, [ 7 ] and mouse, [ 8 ] have played a crucial role in advancing our knowledge of sepsis‐induced muscle atrophy.…”
Section: Introductionmentioning
confidence: 99%
“…There is an increasing understanding of the role played by skeletal muscle in the immune response and inflammation, mainly on the activation of the innate immune system in muscle [ 24 , 25 ]. According to an emergent hypothesis, skeletal muscle is now regarded as a component of the innate immune system, with primary importance in the response to bacterial infection, as summarized in Figure 1 .…”
Section: The Innate Immune System In Musclementioning
confidence: 99%
“…called metabolism-associated molecular patterns (MAMPS) are capable of activating PRRs [ 26 ]. Toll-like receptors (TLRs), which are a major component of the native immunity afferent limb ( Figure 1 ) [ 28 ], can activate transcription factors that up-regulate the expression of pro-inflammatory cytokines in several cell types and tissues, including skeletal muscle [ 25 , 26 , 27 , 28 ]. Both TLRs’ functions and signaling are dependent on their location, with receptors located on the cell surface (i.e., TLR1, TLR2, TLR4, TLR5, TLR6 and TLR10) usually recognizing pathogenic components, such as proteins (LPS and flagellin) or lipids (mainly lipoproteins).…”
Section: The Innate Immune System In Musclementioning
confidence: 99%
See 1 more Smart Citation